Real‐world treatment outcomes of immune checkpoint inhibitors used off‐label in oncology: A comprehensive cancer institution experience - Sandra Fontanals; Anna Esteve; Andrea González; Cristina Ibáñez; Ricard Mesía; Ana Clopés (Wiley, 2024)
Abstract Off‐label use (OLU) is quite common in oncology due to the complexity of cancer and the time‐consuming regulatory process. However, outcomes of OLU in cancer treatment remain unclear. This study aimed to evaluate the overall survival (OS), event‐free survival (EFS), duration of treatment (DOT), and reason for treatment discontinuation in patients receiving immune checkpoint inhibitors (ICI) as OLU for solid tumors from 2011 to 2020. The study collected data on 356 episodes (353 patients), with a median age of 64.4 years, 36.2% women, and 14.6% ECOG ≥ 2. Median OS was 15.7 (11.9-18.7) months, and median EFS was 5.4 (3.8-6.6) months. Men, patients with metastatic disease or ECOG‐PS higher than 1, had worse survival outcomes. The findings derived from this study provide valuable information regarding the real‐world use of ICI‐OLU and contributes to enhancing the decision‐making process for individuals with cancer. Further research on immunotherapy outcomes of OLU in cancer is needed.